Dykha O.V. Approximate wear contact problem for cylindrical bearing with allowance for slip friction - Диха, О. В. (Problems of Tribology, 2018)
An approximate method of determining the distribution of contact pressure in a cylindrical bearing of a slide is proposed. In the solution, the experimental dependence of the dimensions of the contact arc in the bearing on external immittence is additionally used. The functional problem is obtained on the basis of the least squares method as a deviation of the experimental function from the integral equilibrium condition. An iteration procedure is proposed to obtain the estimated values ​​of kinetics of wear and contact parameters. For a more precise solution of the contact problem, an algorithm for taking into account tangential stresses from friction is given